Perencanaan Kolam Retensi Pada Perumahan Mutiara Witayu Kecamatan Rumbai Koata Pekanbaru - Rio Novi Awan; Imam Suprayogi; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Flooding in Mutiara Witayu Recidence caused a big problem for the local communities. This situation led the government taking an action to relocate and plan a construction of retention pond as a settlement of the flood in the region. The purpose of this study was to get a sufficient retention pond capacity to accommodate the flood discharge at the sites. During it’s planning, hydrological analysis was conducted with rainfall data from the Office of Hydrology station for 20 years. Log Person III probability distribution and 5 year retense were used for the analysis. EPA SWMM program was used to analyze the flow of runoff existing in this study. The flooding problem was due to the runoff water which could not flow out into the outfall caused by the operation of the sluice. So it was necessary to accommodate the construction of retention pond during the discharge of the runoff of rainwater. The retention pond with a capacity of 23,000 m3 with a maximum depth of 1 m and ponded area of 23,000 m2, was planned in the study site. Based on the running program, it was found that the addition of a retention pond with that capacity could effectively accommodate the flood discharge at the sites. The cost required to build retention pond was Rp. 7,810,000,700.00 (Seven Billion Eight Hundred and Ten Million Seven Hundred Rupiahs).Keywords : Mutiara Witayu Recident, Flood, EPA SWMM, Retention Pond, Engineering Estimate